Predictive value of 3D imaging to guide implant selection in immediate breast reconstruction. (March 2022) - Yu, Monica; Mahoney, Mary-Helen; Soon, Gordon; Pinchuk, Brian; Somogyi, Ron
SUMMARY: Background: Pre-operative estimation of breast mound volume for immediate breast reconstruction is necessary for operative planning, especially in direct-to-implant reconstruction. Our purpose was to investigate the relationship between pre-operative predictions of breast mound weight from 3D imaging and actual mastectomy weight and implant size. Methods: A retrospective chart review of all patients who had previously undergone nipple-sparing mastectomy (NSM) by a single surgeon was performed. Pre-operative 3D images were reviewed and calculations of breast mound weight were performed by three independent reviewers. Intra-operative mastectomy weight and final implant weight were collected from patient charts. A regression analysis between calculated and actual values was performed. Results: There were 59 reconstructed breasts included. Pre-operative 3D imaging-guided breast weight calculations were similar across reviewers (R=0.96). Pre-operative calculations of breast weight were 49.4g (SD=134.0) smaller than actual mastectomy specimens. Mastectomy specimens were 41.0g (SD=130.2) smaller than final implant sizes. Thereby, the relationship was as follows: Pre-operative calculated breast weight < actual Mastectomy weight < implant weight. Mastectomy weight and final implant size had linear relationships with pre-operative calculations of breast weight. Formulas for predicting mastectomy weight [mastectomy weight = 63.2 + 0.95 (pre-operative calculated weight)] and implant size [Implant weight = 209.7+ 0.56 (pre-operative calculated weight)] from pre-operative calculations of breast weight were generated. Conclusions: Three-dimensional scanning technologies may be a useful tool to predict implant sizes for direct-to-implant breast reconstruction. Final implant size was heavier than intra-operative mastectomy weight and pre-operative calculated breast mound weight.